2012
DOI: 10.4308/hjb.19.4.155
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Streptomyces spp. as Biocontrol Agents of Rice Bacterial Leaf Blight Pathogen (Xanthomonas oryzae pv. oryzae)

Abstract: Xanthomonas oryzae pv. oryzae (Xoo), a causal agent of bacterial leaf blight (BLB), is one of the most important pathogens of rice. The effectiveness of ten Streptomyces spp. isolates in suppressing Xoo disease was assessed in planta and in vitro. In planta experiments were carried out in a greenhouse and arranged in a randomized completely block design (RCBD) with three replications. Twenty treatments were tested which included plants inoculated with both Streptomyces spp. and Xoo, and plants inoculated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 28 publications
1
25
0
3
Order By: Relevance
“…Suspensi bakteri diinfiltrasikan pada daun tembakau. Reaksi hipersensitif diamati pada 24-48 jam setelah inokulasi (Schaad et al 2001) Tabel 3 Daya hambat bakteri dari Imperata cylindrica terhadap Rigidoporus microporus dapat digunakan untuk mendeteksi adanya mekanisme antibiosis yang terjadi pada aktivitas pengendalian oleh agens hayati (Munif et al 2012;Hastuti 2012;Khaerani et al 2012). Antibiosis adalah penghambatan satu atau lebih organisme oleh senyawa bioaktif berupa antibiotik, enzim pendegradasi dinding sel, atau senyawa volatil yang diproduksi oleh organisme lain.…”
Section: Uji Agens Hayatiunclassified
“…Suspensi bakteri diinfiltrasikan pada daun tembakau. Reaksi hipersensitif diamati pada 24-48 jam setelah inokulasi (Schaad et al 2001) Tabel 3 Daya hambat bakteri dari Imperata cylindrica terhadap Rigidoporus microporus dapat digunakan untuk mendeteksi adanya mekanisme antibiosis yang terjadi pada aktivitas pengendalian oleh agens hayati (Munif et al 2012;Hastuti 2012;Khaerani et al 2012). Antibiosis adalah penghambatan satu atau lebih organisme oleh senyawa bioaktif berupa antibiotik, enzim pendegradasi dinding sel, atau senyawa volatil yang diproduksi oleh organisme lain.…”
Section: Uji Agens Hayatiunclassified
“…Penghambatan patogen X. oryzae pv. oryzae oleh bakteri probiotik R. pickettii TT47 diduga terkait dengan kemampuan bakteri (Hastuti et al 2012) serta produksi siderofor, enzim fosfatase, enzim peroksidase dan HCN oleh P. diminuta A6 (Agustiansyah et al 2013). Pelet yang mengandung bakteri probiotik mampu mempertahankan viabilitas benih padi terinfeksi X. oryzae pv.…”
Section: Pembahasanunclassified
“…Recently, an endophytic Streptomyces strain showed its biocontrol ability against rice bacterial leaf blight by inhibition of Xoo growth, but the active compound was not characterized (Hastuti et al . ). Moreover, Streptomyces toxytricini VN08‐A‐12 was selected from 2690 Actinomycetes strains by strong inhibitory activities against the growth of different races of Xoo .…”
Section: Introductionmentioning
confidence: 97%
“…Although several studies have been focused on induction of plant defence mechanism for biocontrol of fungal disease (Zhao et al 2012;Palaniyandi et al 2013b), none has been reported in biological control of Xoo by indirect mechanism. Recently, an endophytic Streptomyces strain showed its biocontrol ability against rice bacterial leaf blight by inhibition of Xoo growth, but the active compound was not characterized (Hastuti et al 2012). Moreover, Streptomyces toxytricini VN08-A-12 was selected from 2690 Actinomycetes strains by strong inhibitory activities against the growth of different races of Xoo.…”
Section: Introductionmentioning
confidence: 99%